Intellectual Property Rights Protection, Ownership, and Innovation: Evidence from China - Fang, Lily H.; Lerner, Josh; Wu, Chaopeng (Review of Financial Studies, 2017)
Using a difference-in-differences approach, we study how intellectual property right (IPR) protection affects innovation in China in the years around the privatizations of state-owned enterprises (SOEs). Innovation increases after SOE privatizations, and this increase is larger in cities with strong IPR protection. Our results support theoretical arguments that IPR protection strengthens firms’ incentives to innovate and that private sector firms are more sensitive to IPR protection than SOEs. Received June 17, 2015; editorial decision November 23, 2016 by Editor Andrew Karolyi.